2015
DOI: 10.1186/s12943-015-0361-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the PI3K/Akt/mTOR signalling pathway in human cancers induced by infection with human papillomaviruses

Abstract: Infection with Human papillomaviruses (HPVs) leads to the development of a wide-range of cancers, accounting for 5% of all human cancers. A prominent example is cervical cancer, one of the leading causes of cancer death in women worldwide. It has been well established that tumor development and progression induced by HPV infection is driven by the sustained expression of two oncogenes E6 and E7. The expression of E6 and E7 not only inhibits the tumor suppressors p53 and Rb, but also alters additional signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
153
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 152 publications
(231 reference statements)
2
153
0
4
Order By: Relevance
“…Mutation data from many independent studies showed mutations in PIK3CA and PTEN in various proportions in cervical cancer (13%‐23% in PIK3CA, 5%‐8% in PTEN) 20. A recent review found that HPV oncogenes E6/E7/E5 enhance the PI3K/AKT/mTOR signalling pathway by directly activating PI3K and the downstream AKT and p70S6K, which consequently modulates tumour initiation and progression as well as patient outcome in cervical cancer 21. As a negative regulatory molecule of the PI3K/AKT pathway, INPP4B has been reported to have tumour suppression effects in various tumours 9, 10, 11, 12.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation data from many independent studies showed mutations in PIK3CA and PTEN in various proportions in cervical cancer (13%‐23% in PIK3CA, 5%‐8% in PTEN) 20. A recent review found that HPV oncogenes E6/E7/E5 enhance the PI3K/AKT/mTOR signalling pathway by directly activating PI3K and the downstream AKT and p70S6K, which consequently modulates tumour initiation and progression as well as patient outcome in cervical cancer 21. As a negative regulatory molecule of the PI3K/AKT pathway, INPP4B has been reported to have tumour suppression effects in various tumours 9, 10, 11, 12.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang and colleagues published a comprehensive review highlighting how HPV's oncogenic proteins E5, E6, E7 enhance PI3K pathway signaling via direct activation of PI3K as well as downstream AKT and rpS6K. In addition, these proteins appear to induce ligand dependent signaling indirectly through epidermal growth factor receptor (EGFR) [56,57]. The specific activities of E5, E6, and E7 have been recently reviewed by Chen and colleagues.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…The results, therefore, suggest indirect inhibiting mechanisms of mTOR by the inhibition of upstream regulators as PI3K which are affected by activated extracellular protein ligands like EGFR. The activation of mTOR in HPV-related tumors occurs in more than 60%, outlining the significant role of mTOR in the appearance of p16-associated tumors (52). In our previous work we already showed a distinct decrease of mTOR expression in both p16-negative and p16-positive squamous cancer cells by direct mTOR inhibition (53).…”
Section: Discussionmentioning
confidence: 87%
“…In our previous work we already showed a distinct decrease of mTOR expression in both p16-negative and p16-positive squamous cancer cells by direct mTOR inhibition (53). The activity of mTOR can be regulated through AKT signalling and through direct enhanced phosphorylation of mTOR through p16-associated oncoprotein E6 (52). Indirect inhibition of mTOR through PDGFR inhibition or EGFR inhibition significantly reduced mTOR expression in p16-associated tumor cells.…”
Section: Discussionmentioning
confidence: 99%